Improved Sensitivity of a Sensor Based on Metallic Nano-cylinder Coated with Graphene - Hedhy, Manel; Ouerghi, Faouzi; Zeng, Shuwen; AbdelMalek, Fathi (Plasmonics (Norwell, Mass.), 2024)
This paper introduces a highly sensitive biosensor based on a plasmonic nanostructure-enhanced resonance effect. The sensor exploits a hexagonal photonic crystal composed of plasmonic nano-cylinders, including a graphene nano-cylinder as a defect, which can considerably increase the concentration of electric fields. This amplification enables the detection of tiny variations in refractive indices linked to a laser source for plasmonic excitation. Each defect consists of a hollow metallic cylinder surrounded by graphene, all within a metallic matrix. During the sensing process, surface plasmon polaritons interact with the core-guided modes of the patterns, which are subsequently filled with the analytes to be measured. The nano-cylinders’ width is optimized to take advantage of their unique optical properties in nanoscale confinement, resulting in high sensitivity. The sensor achieves an impressive sensitivity of 17,750 nm/RIU (refractive index unit) and a FoM of 2218 (RIU −1 ) for n = 1.456 at the optimum value of Δ R = ( R out − R in ) = 200 nm. These metallic cylindrical channels exhibit distinct responses to different analytes across a wide range of Δ R , enabling simultaneous detection of various types of biomolecules. These exceptional properties make the sensor suitable for a broad range of applications, including real-time chemical and biological sensing. Furthermore, it offers the potential to create compact devices for measuring different refractive indices.